Synthesis of palm based biolubricant in an oscillatory flow reactor (OFR) - Koh, May Ying; Mohd. Ghazi, Tinia Idaty; Idris, Azni (Elsevier, 2014)
Plant-based oils are drawing great attention as potential alternative biodegradable lubricant base stocks with their attractive properties of being renewable, non-toxic and environmentally friendly. In the present study, oscillatory flow mixing (OFM) technology was applied in the production of palm biolubricant via transesterification of palm methyl ester (PME) with trimethylolpropane (TMP) by using sodium methoxide (CH3ONa) as the catalyst under vacuum conditions. The optimum operating temperature was recorded at 140 °C, based on the maximal conversion of PME to trimethylolpropane ester (TE) achieved and the reaction was found to follow a second order reaction with 99.6 kJ/mol as the total activation energy required. OFR can effectively promote uniform mixing and enhance the engineering performance within the reactor, thus leading to a time saving of more than two-fold compared to the reports of previous researchers. The properties of the synthesized palm biolubricant were also found to be comparable to the other plant based biolubricants.